Neurometabolite Levels in Alcohol Use Disorder Patients During Baclofen Treatment and Prediction of Relapse to Heavy Drinking - Morley, Kirsten C.; Lagopoulos, Jim; Logge, Warren; Chitty, Kate; Baillie, Andrew; Haber, Paul S. (Frontiers in Psychiatry, 2018)
Background and aims: Baclofen, a GABAb agonist, is used as a treatment for alcohol dependence. We aimed to examine brain metabolites following administration of baclofen or placebo in alcohol dependent individuals enrolled in a randomised placebo-controlled trial. Methods: Participants included 31 alcohol dependent individuals (recent drinking: N = 16; and abstinent: N = 15) who had received daily baclofen (BAC = 20) or placebo (PL = 11) for at least 2 weeks (average 17 days). Using in vivo proton magnetic resonance spectroscopy (1H-MRS), spectra from the right parietal lobe were analysed to obtain measures of GABA, Glutamate (Glu), Glutathione (GSH) and N-Acetyl Apartate (NAA) 120 minutes following administration of PL, 10 mg or 25 mg BAC. Results: When weighting alcohol dependent participants according to recent alcohol consumption (within 24 hours), there were significant differences between BAC and PL on parietal concentrations of GSH (p < 0.01) and NAA (p < 0.05). Multiple linear regression revealed a significant predictive effect of GSH on heavy drinking days at 12 week follow-up (Model: F =14.28, R2 = 0.85; GSH: B = -1.22, p = 0.01) and also percentage days abstinent at 12 week follow-up (Model: F =6.50, R2 = 0.72; GSH: B = 0.99, p = 0.06). Conclusion: Our data suggests that the effect of baclofen may be mediated by increased parietal concentrations of the antioxidant GSH and NAA in recently drinking alcohol dependent patients. GSH/Cr levels were also predictive of improved drinking outcomes in the trial and suggests a role for neural oxidative stress in alcohol use disorder.